miR27a, a Fine-Tuning Molecule, Interacts With Growth Hormone (GH) Signaling and Ornithine Decarboxylase (ODC) via Targeting STAT5 - Çoker-Gürkan, Ajda; KOYUNCU, KADRİYE; ARISAN, ELİF DAMLA; YERLİKAYA, PINAR OBAKAN (Springer Wien, 2022)
Autocrine growth hormone (GH) expression triggers cell proliferation, invasion-metastasis in vitro and in vivo models, but GH gene mutations inhibit postnatal growth. Natural polyamines (PA); putrescine, spermidine, spermine trigger cell growth and differentiation. The importance of miR27a has shown to exert a suppressive effect on ornithine decarboxylase (ODC) expression in dwarf mice models. We aimed to modulate the role of A13S, F166 Delta, T24 GH gene mutations' impact on PA metabolism and epithelial-mesencyhmal transition (EMT) pathway through miR27a. Biologically active GH signaling triggered cell viability, growth, and colony formation, but T24A alteration significantly decreases aggressive profiles due to inactive GH signaling through a decline in STAT5 activity and expressions of STAT5, c-myc and ODC. Although statistically significant increase in intracellular PA levels in wt GH signaling HEK293 cells compared to HEK293 cells with a lack of GH signaling, a sharp decline in PA levels measured in each mutant GH expressing HEK293 cells. When we inhibited miR27a, proliferation and colony formation accelerated through a significant increase in putrescine levels and upregulation of ODC, STAT5 expression. In contrast, a substantial decline in GH-mediated colony enlargement observed via ODC, STAT5 downregulation, and PA depletion in both wt and mutant GH expressing HEK293 cell lines by miR27a mimic transfection. In conclusion, T24A mutant GH expression declines the GH signaling through STAT5 activity, and mutant GH signaling decreased cell proliferation, division, and colony formation via EMT inhibition. The autocrine GH-mediated proliferative profiles were under the control of miR27a that depletes intracellular putrescine levels via targeting ODC.
Keywords: EMT Pathway; Growth Hormone; miRNA27a; ODC; Polyamine